ChemInform Abstract: Iron‐Catalyzed Cyclization of Ketoxime Carboxylates and Tertiary Anilines for the Synthesis of Pyridines. Issue 29 (June 2016) - Zhao, Mi‐Na; Ren, Zhi‐Hui; Yu, Le; Wang, Yao‐Yu; Guan, Zheng‐Hui
Abstract: A series of 2, 4, 6‐trisubstituted and 2, 4‐disubstituted pyridines is readily prepared by Fe‐catalyzed reaction of ketoximes (I) and (VI) with tertiary amines.